Risks of the implementation of a comprehensive scientific and technological program aimed at the development of potato breeding and seed production in the Russian Federation - O. A. Yeremchenko; O. V. Cherchenko (Ekonomika Nauki)
In May 2018, the Federal Science and Technology Program for the Development of Agriculture for 2017–2025 was supplemented by the subprogram “Development of potato breeding and seed production in the Russian Federation”, and integrated scientific and technical programs and projects (ISTP) were chosen as the form of its implementation.The risk analysis of the implementation of ISTP in the priority direction under consideration was performed.Particular attention is paid to the problem of attracting industrial customers to the ISTP – agricultural producers who have sufficient resource support and are able to perform the necessary amount of work on growing and bringing to the market potatoes of domestic breeding.It has been suggested that in order to improve the efficiency of project expertise and reduce the risks of unreachability of the stated indicators, it is advisable to carry out the selection of domestic companies – potential beneficiaries of the technologies being developed at the first stages of the ISTP implementation.